Disrupsi Digital dalam Dunia Hukum : Bagaimana Kecerdasan Buatan Mengubah Praktik Hukum di Indonesia? - Vincentius Patria Setyawan (JURNAL HUKUM PELITA, 2025)
This paper examines the digital disruption brought by Artificial Intelligence (AI) and its transformative impact on legal practice in Indonesia. The objective is to analyze how AI is reshaping traditional legal workflows, from legal research and contract drafting to judicial decision support and predictive justice. Using a normative-juridical method with a qualitative approach, this study explores legal, ethical, and institutional implications related to the use of AI in the legal profession. The analysis is based on primary legal sources (statutory regulations) and secondary sources (scientific journals, reports, and expert opinions). Findings show that while AI offers efficiency and accessibility in legal services, it also raises significant challenges including accountability gaps, potential bias in algorithmic processes, and the weakening of human judgment in judicial procedures. The study concludes that Indonesia's legal system must establish clear regulatory frameworks and ethical guidelines to govern the use of AI in law. Such measures are essential to ensure that AI enhances, rather than undermines, justice and legal certainty